Association between Intracranial Arterial Dolichoectasia and Cerebral Small Vessel Disease and Its Underlying Mechanisms - Dao Pei Zhang; Suo Yin; Huai Liang Zhang; Dan Li; Bo Song; Jia Xu Liang (Journal of Stroke, 2020)
Intracranial arterial dolichoectasia (IADE), also known as dilatative arteriopathy of the brain vessels, refers to an increase in the length and diameter of at least one intracranial artery, and accounts for approximately 12% of all patients with stroke. However, the association of IADE with stroke is usually unclear. Cerebral small vessel disease (CSVD) is characterized by pathological changes in the small vessels. Clinically, patients with CSVD can be asymptomatic or present with stroke or cognitive decline. In the past 20 years, a series of studies have strongly promoted an understanding of the association between IADE and CSVD from clinical and pathological perspectives. It has been proposed that IADE and CSVD may be attributed to abnormal vascular remodeling driven by an abnormal matrix metalloproteinase/tissue inhibitor of metalloproteinase pathway. Also, IAD-Erelated hemodynamic changes may result in initiation or progression of CSVD. Additionally, genetic factors are implicated in the pathogenesis of IADE and CSVD. Patients with Fabry’s disease and late-onset Pompe’s disease are prone to developing concomitant IADE and CSVD, and patients with collagen IV alpha 1 or 2 gene (COL4A1/COL4A2) and forkhead box C1 (FOXC1) variants present with IADE and CSVD. Race, strain, familial status, and vascular risk factors may be involved in the pathogenesis of IADE and CSVD. As well, experiments in mice have pointed to genetic strain as a predisposing factor for IADE and CSVD. However, there have been few direct genetic studies aimed towards determining the association between IADE and CSVD. In the future, more clinical and basic research studies are needed to elucidate the causal relationship between IADE and CSVD and the related molecular and genetic mechanisms.